Comparison of sensitivity and specificity of anti-CCP and anti-MCV antibodies in an Iranian cohort of patients with rheumatoid arthritis - Yousefghahari, Behnaz (Babol University of Medical Sciences, 2013)
Background: Anti-CCP is a test commonly used for the diagnosis of rheumatoid arthritis. The aim of this study was to determine the diagnostic values of ACCP compared to anti-MCV in rheumatoid arthritis patients in north of Iran. Methods: The serum samples of 150 RA patients and 75 controls, with the mean age of 49.6+11.8 and 48.8+12 years respectively, were tested using the commercially available ELISA kits for ACCP and anti-MCV. Sensitivity, Specificity were determined and Roc curve were used for comparison between these two groups. Results: The sensitivity of ACCP versus anti-MCV was 85% and 81%, respectively. Specificity was 96% and 95%, respectively. In the RA patients, ACCP was positive in 127 (84.7%) and anti MCV in 121 (80.7%) cases. In the control group, these parameters were positive in 3 (4%) and 4 (5.3%) (p<0.0001 and p<0.0001, respectively). The correlation coefficient for ACCP and anti-MCV was calculated at 0.63 (p<0.001). The area under the curve for ACCP was 0.941±0.015 (p<0.001), anti-MCV was 0.902±0.02 (p<0.001). The measure of agreement (Kappa) for these variables was 0.81. In these patients, there was no correlation between DAS28 and the positivity of these tests. Conclusion: It was concluded, compared to ACCP, anti-MCV has approximately the same accuracy for the diagnosis of rheumatoid arthritis and it does not have additional value.